Video game play and consciousness development: a transpersonal perspective - Gackenbach, Jayne (My University, 2008)
The development of consciousness to higher states is thought to be a natural process by some contemporary psychologists with a transpersonal orientation. Such "higher" states of consciousness can be enhanced with the right cultural amplifier. The most often examined amplifiers are the effects of prayer and meditation. But tools, from early attempts at record keeping with knots in ropes through today's computer mediated communications, also affect cognition and thus ultimately consciousness. In this article the hallmark of electronically mediated interactive environments is examined in terms of its implications for the development of consciousness. That tool is video game play.
Keywords: video games; consciousness